Estimation of Genetic Parameters and Association of Growth Characters in Tinospora cordifolia (Willd.) Miers Ex Hook. F. & Thoms - Usmani, Gufran; Shah, Syed Naseer; Chawhaan, Pravin H.; Mishra, Yogeshwar; Mandal, Asim Kumar (Indian Forester, 2015)
Variability, heritability and character association were studied in 15 populations of Tinospora cordifolia. Highest and lowest genotypic coefficient of variability was observed for shoot length and stem diameter, respectively. Total stem biomass per meter which had high estimates of heritability also had high genetic advance. Significant positive correlation at genotypic level was found between leaf area and shoot fresh weight and root fresh weight.